THE MEANING OF SOCIAL CONSTRUCTION HINDU COMMUNITY EXOGAMY MARRIAGE IN BALI - I Made Pasek Subawa (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
The endogamy mating model reflects an individual's preference for mating within their own group. Endogamy has been widely practiced in many societies and used by various types of groups. The caste system in India requires endogamy. There is strong pressure for them to marry within their own sub-caste and there are strong sanctions against violators. Today's social phenomenon in the life of the Hindu community in Bali shows a change regarding the prohibition of exogamy marriages between clans. Marriages that occur in Hindu communities in Bali in the modern era today are not only carried out endogamy within the tri wangsa group, but also exogamy marriages between the tri wangsa and wangsa jaba groups have often occurred, not even a few have carried out mixed marriages between both groups. Religion as well as between nations and this has received recognition from the community.